Inequalities of Hermite-Hadamard Type for h-Convex Functions on Linear Spaces - Dragomir, S. S. (Proyecciones (Antofagasta), 2025)
Some inequalities of Hermite-Hadamard type for h-convex functions defined on convex subsets in real or complex linear spaces are given. Applications for norm inequalities are provided as well.